Les visites nocturnes au musée, une possibilité de changement de registre de visite pour les visiteurs de la cour Marly du Louvre ? - Floriane Germain (Les Cahiers de l'École du Louvre)
Late-night openings allow museum visitors to come during the evening, for a leisure activity after work, as night begins to fall and daylight is gradually replaced by artificial lighting. A study carried out in the Cour Marly of the Musée du Louvre during the night allows us to learn a little more about the visitor experience, the relationship with the place and the image that visitors have of their visiting practice. The changes observed between day-time and night-time visits raise questions about exhibition registers and their variation.